2005
DOI: 10.1177/0095399704270582
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing the Authentic

Abstract: This article builds upon and extends the work of civic engagement, deliberative democracy, and discourse theorists by critically examining the ways in which civic engagement is currently conceptualized and utilized. Through this analysis, critical oversights, assumptions, and biases concerning the potential of public participation, the nature of who is or is not engaged, and the places where authentic engagement is occurring are revealed. To move the field forward and to prevent scholars and practitioners from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 25 publications
0
2
1
1
Order By: Relevance
“…Congruent with studies that have explored PPI in other settings (Campbell, 2005; Martin, 2008), we found that the majority of participants in our study were highly educated, with professional or managerial backgrounds (although their careers had often ended prematurely because of ill health or caring commitments). We would suggest that there were clear parallels between our participants and Campbell’s notion of the “good citizen”: likeminded individuals from well-educated backgrounds with disposable resources (time and money).…”
Section: Resultscontrasting
confidence: 81%
“…Congruent with studies that have explored PPI in other settings (Campbell, 2005; Martin, 2008), we found that the majority of participants in our study were highly educated, with professional or managerial backgrounds (although their careers had often ended prematurely because of ill health or caring commitments). We would suggest that there were clear parallels between our participants and Campbell’s notion of the “good citizen”: likeminded individuals from well-educated backgrounds with disposable resources (time and money).…”
Section: Resultscontrasting
confidence: 81%
“…Inequities are reproduced because those constructing ideology and policy practices sabotage efforts to articulate alternative understandings of the contributions that women make to society. If social and economic policies centered a concept like provisioning, with its broad understanding of work, anchored in the reality of responsibilities and relationships, it would lead to different discussions about citizenship, civil society, entitlements, and rewards (see Campbell 2005 for one exploration of the possibilities). A model where the market, state, and family are all visible has been advocated by a number of feminist policy scholars (Lister 1997; Skevik 2005; Staeheli and Clarke 2003; Thayer 2000; Vandenberg 2000; Yuval‐Davis 1999).…”
Section: Resultsmentioning
confidence: 99%
“…For some, like Bhai, Grace, and Brendan, these experiences may bring into sharp relief uncomfortable positions of inequality, injustice, and frustration, faced by past and current selves, and potential future selves. This evokes the reflective and "awakening" potential of participation (Campbell, 2005): through PPI, contributors construct new interpretations of their positions within the world, and of the benefits and limitations of these positions.…”
Section: Discussionmentioning
confidence: 99%